Nitrite Cycling in Warming Arctic and Subarctic Waters - Yangjun Chen; Min Chen (Geophysical Research Letters)
Abstract The primary nitrite (NO2−) maximum (PNM) is a typical feature of oceanic nitrogen (N) cycle, yet its characterization in the world ocean remains a gap. By combining the natural abundance of NO2− isotopes with geochemical model, we report for the first time that the formation of Arctic and subarctic PNMs is dominated by ammonia oxidation, while the oxidation of NO2− is the main sink. Notably, NO2− oxidation plays a more important role in Arctic and subarctic waters than in low‐ and mid‐latitude waters. The residence time of NO2− in the PNM further suggests that the NO2− cycle in the Arctic Ocean is more dynamic than in other marine ecosystems. Our findings provide insights into N cycle dynamics in the upper Arctic Ocean ecosystem.